Integrating Artificial Intelligence Into Cancer Care: Enhancing Nursing Practice and Bridging Disparities. - Youran Lee; Yan Wang; Ansah, Osborn Owusu; Jung In Park; Affronti, Mary Louise; Cary Jr., Michael P. (Clinical Journal of Oncology Nursing, 2025)
Artificial intelligence (AI) in cancer care has the potential to transform nursing practice, reduce cancer disparities, and enhance patient outcomes across the continuum of care from prevention, screening, and treatment to survivorship and end-of-life care. Responsible adoption of AI in cancer care requires addressing the mistrust of AI, lack of standardized data elements, concerns about accuracy and reliability, and need to mitigate algorithmic bias. Oncology nurses have a pivotal role in applying AI to health care and addressing these challenges. Enhancing nursing practice with AI requires continuous training and education, ethical considerations, and maintenance of the patient-nurse relationship in the context of AI integration.